2007
DOI: 10.1007/s00276-007-0179-3
|View full text |Cite
|
Sign up to set email alerts
|

Size and location of the fetal diaphragm during the fetal period in human fetuses

Abstract: New data are derived for human fetuses to evaluate diaphragmatic development. Data acquired in this study are believed to contribute to studies of obstetrics, perinatology, forensic medicine and fetal pathology on fetal development of the diaphragm, and diagnosis of its anomalies, pathologies and variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…An increase in the CO diameter with fetal age has been reported in previous studies. 10 On the other hand, we did not find a linear increase in the diameters of CO and FVHs of 13 cases with fetal age ( Table 2). We believe this finding may be related to the variability in the number of HVs and to HVs opening into the IVC within the diaphragm rather than joining the IVC beneath the diaphragm.…”
Section: Variations Of Hepatic Veins Opening Into the Inferior Vena Cavamentioning
confidence: 63%
“…An increase in the CO diameter with fetal age has been reported in previous studies. 10 On the other hand, we did not find a linear increase in the diameters of CO and FVHs of 13 cases with fetal age ( Table 2). We believe this finding may be related to the variability in the number of HVs and to HVs opening into the IVC within the diaphragm rather than joining the IVC beneath the diaphragm.…”
Section: Variations Of Hepatic Veins Opening Into the Inferior Vena Cavamentioning
confidence: 63%
“…Sonographically, the diaphragm appears as a thin, dark, arched line; it usually shows a dome on each side, where the right side seems higher than the left side. However, recent anatomical studies 3 did not find any difference between the height of the left and the right diaphragmatic domes. The costodiaphragmatic recess is most commonly located at the level of the 9th rib.…”
Section: Diaphragmmentioning
confidence: 80%
“…The costodiaphragmatic recess is most commonly located at the level of the 9th rib. 3 The function of the diaphragm, namely breathing, has been the subject of extensive ultrasound research. As early as the 1970s, ultrasound studies of fetal breathing movements (FBMs) in human fetuses showed that their presence was indicative of well-being, while the absence of FBM, though less reliably, was a sign of pregnancy disorder.…”
Section: Diaphragmmentioning
confidence: 99%
“…There are several studies on fetal biometry for people living in Turkiye [21][22][23][24][25][26][27][28]. However, there is no standard chart of each fetal biometric parameter for the Turkish population, especially for the Central Anatolian population.…”
Section: Discussionmentioning
confidence: 99%